Physical and mechanical properties of bilayer cemented tungsten carbide and steel fabricated through die compaction process - Job Oluwatosin, Ojo-Kupoluyi (2016)
In this study, a bimaterial of cemented tungsten carbide (WC) and steel was fabricated via die compaction process as it combines the hardness of WC and toughness of steel used for making machine tools. Major challenges related to this study is in two folds; firstly, the cobalt (Co) commonly used as WC binder has been reported to be scarce in supply and toxic making the International Agency for Research on Cancer (IARC) classify sintered WC–Co hard metals as carcinogenic and harmful to humans. Secondly, microstructural analysis has revealed the formation of detrimental phase (eta carbide) in co-sintered tungsten carbide and steel bilayer resulting in the deterioration of properties of this bilayer. Therefore, there is a need to replace cobalt with iron (Fe) as the binder, and also control the carbon (C) content in Fe as part of the composition in order to suppress eta carbide formation. WC–Fe–C and Fe–W–C bimaterial was fabricated with varying carbon content of Fe part composition (Fe–6W–xC, x = 0.2, 0.4, 0.6 and 0.8 wt.%). Sintering temperature was varied (1280oC, 1290oC &1295oC) to control the sintering kinetics and limit mismatch between layers that commonly occur in bilayer compacts. Microstructural analysis revealed significant reduction of the eta carbide phase with increasing carbon content as the bilayer specimen, MC–0.8 with the highest carbon addition (0.8 wt.%) sintered at 1280oC was observed to have vestigial trace of eta carbide phase when compared to other samples. An improved density results (6.1%) with increased carbon level resulting in stronger interfacial bond was observed in bilayer samples sintered at 1280oC, while weak interfacial bond owing to shrinkage mismatch was observed in samples sintered at 1295oC. Hardness values increased with increasing carbon addition at all sintering temperatures (At 1280oC, MC–0.2 = 132.80 & 692.93 kgfmm-2 while MC–0.8 = 150.97 & 735.70 kgfmm-2 for Fe and WC parts respectively) which was attributed to the reduction of eta carbide formation. Through diametral compression test, bilayer samples sintered at 1280oC were found to possess higher values of tensile strength which significantly increased from 45.10 MPa to 55.75 MPa with increase in carbon content.